Growth Response and Production of Cabbage (Brassica Olera Var. Capitata) on Various Kinds of NPK and Organic Fertilizers - Rosmadelina Purba; Irawaty Rosaline; Ringkop Situmeang; Christin Imelda Girsang; Wahyunita Sitinjak (Postgraduate, University of Mataram, 2023)
This study was conducted in Pematang Bandar district of Simalungun regency at an altitude of Â±150 meters above sea level. This study investigated the growth response and production of cabbage (brassica olera var. capitata) to various types of NPK and organic fertilizers. This study used a randomized block design (RBD) with two treatment factors. The first factor was applying various types of organic fertilizers consisting of three dosage levels: P1 = 4 kg/plot cow manure; P2 = 0.8 kg/plot organic fertilizer by PETROGANIK; P3 = 1.2 kg/plot organic fertilizer by MABAR. The second factor was applying NPK fertilizer consisting of three dose levels: N1 = 3.5 g/plot; N2 = 5 g/plot; N3 = 6.5 g/plot. The parameters observed were: plant height (cm) 2.4 and 6 WAP (week after planting); total leaf (blades); crop formation speed; crop weight per plant (kg); crop weight per plot (kg). The results showed a real response in applying various types of NPK and organic fertilizers. In addition, there was a real response in applying various types of NPK and organic fertilizers to plant height, total leave, crop formation speed, crop weight per plant, and crop weight per plot on cabbage growth and production.